Social Identity of Non-Moslem Students In Muhammadiyah Universities: Identitas Sosial Mahasiswa Non-Muslim Di Perguruan Tinggi Muhammadiyah - Hamzah, Imam Faisal; Akbar, Zaldhi Yusuf; Grafiyana, Gisella Arnis (Universitas Muhammadiyah Sidoarjo, 2021)
Education in Indonesia, especially higher education institutions, has a role to build interaction between religious adherents. How is this experience of tolerance in religiously based higher education institutions where the majority of students and staff are religious according to the institution. One of the largest religious-based higher education networks in Indonesia is the Muhammadiyah Universities or Perguruan Tinggi Muhammadiyah (PTM) network. Muhammadiyah as one of the largest Islamic organizations in Indonesia which has a network of higher education spread across various parts of Indonesia where students studying have diverse religious backgrounds. This study aimed to examine the dynamics of social identity in the experience of non-Moslem students at Muhammadiyah College. This research uses qualitative research methods using Interpretative Phenomenological Analysis (IPA). Six participants, Christian, Catholic, Hindu, and Buddhist from four Muhammadiyah College in the province of Central Java - Indonesia, were interviewed and analyzed to obtain core themes. The results of this study produced five superordinate themes, namely the influence of the environment, personal characteristics, perceptions of the religion adopted, experience as a Muhammadiyah College Student, and perceptions of Islam and Muhammadiyah. The conclusion of this study shows the psychological dynamics of non-Muslim students shape the perception of Islam itself as a religion, also Muhammadiyah as an Islamic organization.